DILEMA ANTARA HOBI DAN BISNIS PERDAGANGAN BURUNG SERTA KONSERVASI BURUNG - Iskandar, Johan (Departemen Kimia, 2014)
Paper discusses result of study on the development of hobby on bird keeping, bird song contest, bird trade business, and conservation strategy for bird sustainable use, based on case study undertaken in the Bandung urban and surrounding areas. The combination of qualitative and quantitative method with descriptive analysis was used in this study. The result of study shows that based on direct inventory it was recorded 96 bird species of 24 families which were being kept by thirty respondents. Among the total species, 29 species and races were recorded as dominant, namely anis merah (Zoothera citrina), murai batu (Copsychus malabaricus), ciblek (Prinia familiaris), several races of kenari (Serinus canarinus), several races of lovebird (Agapornis spp), bentet/toed (Lanius schach), several races of pleci/burung kacamata (Zosterops palpebrosa), robin (Leothrix sp), and perkutut (Geopelia striata). Nowadays, the hobby of bird keeping in the cages has tended to increase caused of development of regular song bird contest in the local, regional and national level. Based on this study, it was recorded that fiveteen bird species have commonly entertained in the local song bird contests by the bird lovers in Bandung urban and surrounding areas. Development of the increasing bird keeping hobby and song bird contests have tended to develop bird trading in the urban bird markets and increasing bird hunting in the villages. Therefore, the activity of bird keeping hobby, song bird contests, and bird trading have been dilemma. On the one hand, these activities have provided some benefits. For example, it has developed the bird trading business and bird captive breeding undertaken by the bird lover communities and providing some economic benefits. On the other hands, these activities have affected to dramatically bird population decrease in nature due to increasing bird hunting in villages. Even some rare birds have high risk to be decrease and maybe disappear in some village areas in the near future. Therefore, to sustainable utilize bird species for fulfilling the hobby of bird keeping, bird contests and bird trading purpose; the conservation effort based on community participation is essentially needed.